Fatty Acid Profile of Roots and Aerial Parts of Ruscus hyrcanus Woronow - Mir Babak Bahadori; Solmaz Asnaashari; Hossein Nazemiyeh (Pharmaceutical Sciences, 2019)
Background: Ruscus specie are used as traditional medicine, food, and foliage. The aim of this work is the determination of fatty acid composition of Ruscus hyrcanus as a native medicinal plant of Iran for the first time together with comparison of different esterification methods. Methods: Two different esterification methods were used for preparation of esterified fatty acids from different extracts of underground and aerial parts of the herb. GC/MS analysis were used for identification and quantification of fatty acids. Finally, the results were compared. Results: Findings showed that R. hyrcanus is rich in essential fatty acids such as linoleic acid (13-25%) and linolenic acid (23-44%). Also, oil samples contain remarkable amount of palmitic acid (19-57%). Conclusion: The results showed that R. hyrcanus could be considered as a source of essential fatty acids. Also, it could be concluded that a simple esterification method with methanolic KOH and 2 min vortex is suitable for fatty acid analysis of Ruscus species.